The synergistic impact of Spirulina and Sulfate reducing bacteria on lettuce growth in Cadmium contaminated soil - Maryam Seifikalhor; Mojgan Latifi; Neda Nasiri Almanghadim; Zahra Akbar-Tajari; Anahita Ahangir; Seyedeh Batool Hassani; Neda Soltani; Hossein Sadeghi; Elyas Eghbal; Zahra Fallahi; Nazim S. Gruda (Scientific Reports)
Abstract Cadmium (Cd) contamination is a critical environmental issue, adversely affecting plant growth and agricultural productivity. While numerous studies have explored the role of various bacteria in mitigating heavy metal toxicity, the specific impacts of sulfate-reducing bacteria ( Desulfovibrio desulfuricans, SRB) and the cyanobacterium Spirulina (Arthrospira platensis, SP), both individually and in combination, on Cd-contaminated plants remain underexplored. This study investigates the effects of SRB and SP on lettuce plants exposed to Cd contamination, aiming to enhance our understanding of their potential in alleviating Cd toxicity and promoting plant health. Results revealed that Cd contamination significantly reduced root growth in all treatments except for the combined application of SRB and SP. This combination also led to a marked decrease in leaf Cd content and improved leaf area, particularly under Cd stress. Furthermore, SP and SRB together increased the relative water content in contaminated soils, and SRB alone induced hydrogen peroxide production in non-contaminated soils. The co-application of SRB and SP significantly boosted catalase and superoxide dismutase activities, enhancing photosynthetic capacity and overall plant growth under Cd stress. These findings underscore the promising potential of using SRB and SP synergistically to mitigate Cd-induced challenges in lettuce cultivation, offering a viable strategy to improve crop productivity in contaminated environments.